2010
DOI: 10.1080/15299730903143600
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Analysis of Voice Hearing in Chronic PTSD: Potential Associated Mechanisms

Abstract: This research investigated auditory hallucinations (AH) in a sample with chronic posttraumatic stress disorder (PTSD) and examined dissociation and thought suppression as potential associated mechanisms. In all, 40 individuals with PTSD were assessed on the hallucinations subscale of the Positive and Negative Syndrome Scale and on measures of dissociation and thought suppression. Half of the sample reported AH (n = 20, 50%). Those reporting AH had higher general and pathological dissociation scores but did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 35 publications
2
75
0
1
Order By: Relevance
“…However, this argument is not empirically supported (Hardy et al, 2005;Anketell et al, 2010;Corstens and Longden, 2013), as we address in Section "Trauma, SZ-AVH, and PTSD-AVH. "…”
Section: The Phenomenology Of Avh In Ptsd and Schizophrenia Argumentsmentioning
confidence: 83%
See 3 more Smart Citations
“…However, this argument is not empirically supported (Hardy et al, 2005;Anketell et al, 2010;Corstens and Longden, 2013), as we address in Section "Trauma, SZ-AVH, and PTSD-AVH. "…”
Section: The Phenomenology Of Avh In Ptsd and Schizophrenia Argumentsmentioning
confidence: 83%
“…They are also found with notable regularity in post-traumatic stress disorder (PTSD; Butler et al, 1996;Anketell et al, 2010;Brewin and Patel, 2010). In the most studied sub-group of people with PTSD, military veterans, recent studies have reported an AVH prevalence ranging from 50-67% (Holmes and Tinnin, 1995;Anketell et al, 2010;Brewin and Patel, 2010).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Specifically, Varese, Barkus et al (2012) found that dissociation precedes voice onset, and mediates the relationship between sexual abuse and voice-proneness (see also Anketell et al, 2010;Moskowitz & Corstens, 2007;Moskowitz, Read, Farrelly, Rudegeair, & Williams, 2009).…”
Section: Does Dissociation Mediate Voice Hearing?mentioning
confidence: 99%